Pharmacokinetics, Pharmacodynamics and Antiviral Efficacy of the MEK Inhibitor Zapnometinib in Animal Models and in Humans - Koch-Heier, Julia; Schönsiegel, Annika; Waidele, Lara Maria; Volk, Julian; Füll, Yvonne; Wallasch, Christian; Canisius, Sebastian; Burnet, Michael; Planz, Oliver (Frontiers in Pharmacology, 2022)
The MEK inhibitor zapnometinib is in development to treat acute viral infections like COVID-19 and influenza. While the antiviral efficacy of zapnometinib is well documented, further data on target engagement/pharmacodynamics (PD) and pharmacokinetics (PK) are needed. Here, we report zapnometinib PK and PD parameters in mice, hamsters, dogs, and healthy human volunteers. Mice received 25 mg/kg/day zapnometinib (12.5 mg/kg p.o. twice daily, 8 h interval). Syrian hamsters received 30 mg/kg (15 mg/kg twice daily) or 60 mg/kg/day once daily. Beagle dogs were administered 300 mg/kg/day, and healthy human volunteers were administered 100, 300, 600 and 900 mg zapnometinib (once daily p.o.). Regardless of species or formulation, zapnometinib maximum plasma concentration (Cmax) was reached between 2-4 h after administration with an elimination half-life of 4-5 h in dogs, 8 h in mice or hamsters and 19 h in human subjects. Doses were sufficient to cause up to 80% MEK inhibition. Across all species approximately 10 µg/ml zapnometinib was appropriate to inhibit 50% of PBMC MEK activity. In mice, a 50-80% reduction of MEK was sufficient to reduce influenza virus titer in the lungs by more than 90%. In general, while >50% MEK inhibition was reached in vivo at most doses, 80% inhibition in PBMCs required significantly higher doses and appeared to be the practical maximal level obtained in vivo. However, the period of reduced pERK, a measure of MEK inhibition, was maintained even after elimination of zapnometinib from plasma, suggesting a sustained effect on MEK consistent with regulatory effects or a slow off-rate. These data suggest a target plasma Cmax of at least 10 µg/ml zapnometinib in further clinical studies.